Lecturers Acceptance Of Podcast In South-West Nigeria Federal Universities - Emmanuel, Adu Ifedayo (2020)
This study addressed factors regarding lecturers’ acceptance of podcast in south-west Nigeria Federal universities. Hence, this study investigated the significant influence of independent factors on a dependent factor. Also, the significant mediating impact of a mediating factor on the relationship between independent and dependent factors was considered.